Хроніка депортацій 1944–1946 рр. очима лемків (зі спогадів переселенців) - Чаплик, К. (Народна творчість та етнографія, 2008)
Chronicles of Deportations in 1944–1946 Through the Eyes of Lemky article is based on resettlers’ memories and covers some issues of spiritual and material cultures of Lemky, especially their life, household, religion, dialect, national costume, song folklore etc. We are happy to publish memories of Nina Yakivna Bayko, who was the member of outstanding The Baykos Sisters Trio. In 1953 they introduced the Ukrainians the culture and songs of Lemky. Having been originated from Lemkivschina the trio became the most active popularizer and promoter of native song. Thanks to three sisters Mariya, Danyila and Nina and such composers as Philaret and Mykola Kolessas, K. Stetsenko, Yu. Korchynsky, B. Filts, M. Popenko, I. Maychyk, H. Vereta, Ye. Kozak, O. Hram, V. Lystopad, O. Yakovchuk, Ya. Yaroslavenko the Ukrainians could hear songs of Lemky. The composers helped to renew the tradition of Lemky’s live performance.